CORRELATION OF DEMOGRAPHIC AND ANTHROPOMETRIC FACTORS WITH PULMONARY ARTERIAL OBSTRUCTION INDEX AND IMAGING MARKERS OF RIGHT HEART STRAIN IN PATIENTS WITH ACUTE PULMONARY EMBOLISM - Nikolova, Sonja (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Background: Acute pulmonary embolism is a potentially life-threatening condition often accompanied by right heart strain. Computed tomography pulmonary angiography is the preferred imaging modality for assessing both vascular obstruction and cardiac involvement. The impact of demographic and anthropometric factors on imaging biomarkers of right heart strain, such as the pulmonary arterial obstruction index, remains insufficiently investigated.  Methods: This prospective study included 119 patients with confirmed acute pulmonary embolism who underwent computed tomography pulmonary angiography and follow-up echocardiographic evaluation. Demographic (age, sex) and anthropometric (body weight) variables were analyzed in relation to the obstruction index and computed tomography indicators of right heart strain.  Results: The cohort was nearly gender-balanced, with a mean age of 57.8 years. While male patients had higher mean obstruction index and ventricular diameter ratios, these differences were not statistically significant. Significant sex-based differences were observed in aortic and inferior vena cava diameters. Increasing age was significantly associated with larger vessel diameters and a higher prevalence of contrast reflux in the inferior vena cava. Higher body weight correlated with increased vessel dimensions, but not with the obstruction index or ventricular ratios.  Conclusions: Age and body weight are significantly associated with selected imaging markers of right heart strain in acute pulmonary embolism. These results highlight the importance of adjusting computed tomography interpretation based on patient characteristics. Keywords:  acute pulmonary embolism, computed tomography pulmonary angiography, pulmonary arterial obstruction index, right heart strain, ventricular diameter ratio, inferior vena cava reflux